Effect of age upon the induction and maintenance of anticoagulation with warfarin. Issue 833 (March 1995) - Gladman, J. R.; Dolan, G.
Abstract : We aimed to examine the effect of age upon the control of anticoagulation with warfarin in ordinary clinical practice, using a retrospective examination of routine anticoagulation clinic records from the University Hospital, Nottingham. Considerable over-anticoagulation (international normalisation ratio (INR) > 6.0) during induction occurred in 54 (11%) of 495 patients and was more likely in older patients (p < 0.05). Lesser degrees of over-anticoagulation during induction (INR > 4.0) were also more common in older patients, occurring in 58% of those aged 75 or above. Loading doses of warfarin were not reduced in older patients. INR in the maintenance phase rose with age (p < 0.001) despite lower maintenance doses of warfarin (p < 0.001). An INR > 6.0 in the maintenance phase was noted in 24 (3%) of 739 patients and again was more likely in older patients (p < 0.05). Patients using ambulance transport to the clinic were older than those who did not (p < 0.01) and those aged over 75 had shorter intervals between clinic visits (p < 0.01). We conclude that doctors using warfarin therapy do not take sufficient account of the increased sensitivity of older people to warfarin. Hospital anticoagulant policies need implementation and evaluation.